Fatty acids composition of genotypes of Jatropha curcas L., in Colombia - Campuzano-Duque, Luis Fernando (2020)
Introduction. Jatropha curcas L. (JC) is a specie with the potential to use its oil as a biofuel and its quality is recognized by the composition of the fatty acids present. Objective. The objective of this work was the identification and quantification of fatty acids of JC genotypes of the Jatropha Colombia Collection. Materials and methods. During the years 2012-2014 the experiment was conducted in Espinal-Tolima, Colombia, in a randomized complete block design with fifteen genotypes. The lipid profile of the genotypes was determined by chromatography GC-MS and GC-FID. Results. Ten types of fatty acids were detected in the oil: five saturated (myristic, palmitic, margaric, stearic, arachidic); three monounsaturated (palmitoleic, oleic and eicosenoic), and two polyunsaturated (linoleic and linolenic). The proportion was higher in monounsaturated acids (45.44 %) and polyunsaturated acids (34.18 %) and lower in saturated acids (20.37 %). In the monounsaturated, the oleic predominated (44.62 %); in polyunsaturated linoleic (33.95 %) and in saturated palmitic (12.41 %) and stearic (7.43%). The results found allowed the classification of JC oil as monounsaturated-polyunsaturated (oleic-linoleic), which coincided with what was reported worldwide. Conclusion. Based on the lipid profile, it can be inferred that the oil of the fifteen genotypes evaluated in Colombia is suitable for use as biodiesel.